Occupational therapy and obesity: An integrative literature review. Issue 5 (19th June 2013) - Haracz, Kirsti; Ryan, Susan; Hazelton, Michael; James, Carole
<x xml:space="preserve">Abstract</x> Background/aim Obesity is a significant public health concern globally. It is associated with poor physical health, mental health and subjective well‐being and limitations on occupational participation. With its focus on the relationship between occupation, health and well‐being, occupational therapy would appear to be well placed to address both the causes and consequences of obesity. The aim of this review was to explore the scope of the role of occupational therapy practice in this field and the supporting evidence base. Methods Searches were conducted in four online databases and nine occupational therapy journals. Articles were included if they were theoretical, quantitative or qualitative research, explicitly related to occupational therapy and obesity, published in peer‐reviewed journals, in English between 2002 and 2012. All research articles were critically reviewed and thematic analysis was conducted across all of the articles in the review. Results Eight theoretical articles, 12 quantitative and two qualitative research studies were included. Only three were outcome studies. Thematic analysis identified four categories of focus of occupational therapy intervention: health promotion and prevention, increasing physical activity participation, modifying dietary intake and reducing the impact of obesity. Four categories of intervention strategies were also identified; assessment, modifying the environment, education and introducing and adapting occupations. Conclusion and significance The findings of this review suggest a comprehensive role for occupational therapy in addressing obesity. However, the paucity of outcome studies mean that significantly more research is required to further define and provide a strong evidence base for occupational therapy practice in this emerging field.